Dual polarized, slot coupled monostatic antenna with high isolation for 2.4 GHz full duplex applications. Issue 3 (6th November 2019) - Nawaz, Haq; Basit, Muhammad A.; Shaukat, Furqan
Abstract: This paper presents a compact, dual polarized, differentially fed monostatic slot coupled patch antenna with high isolation between transmit (Tx ) and receive (Rx ) ports for 2.4GHz simultaneous transmit and receive (STAR) or in‐band full duplex (IBFD) wireless applications. By using the proposed differential feeding for receive (Rx ) mode operation through symmetrically placed feeds of radiating patch, the self‐interference (SI) is well canceled to demonstrate high Tx ‐Rx interport isolation. The simulation and measurement results for presented IBFD antenna indicate very high levels of interport isolation achieved through differential feeding based self‐interference cancellation (SIC) mechanism. The implemented prototype (validation model) of proposed dual port, dual polarized, slot coupled antenna achieves more than 95 dB peak isolation and 90 dB isolation in 20 MHz bandwidth. Moreover, the achieved Tx ‐Rx isolation is around 85 dB within antenna's 10 dB‐return loss impedance bandwidth of 45 MHz. To the best of our knowledge, these are the highest levels of interport RF isolation reported for dual polarized monostatic patch antenna.